The role of personal ethics and organization ethics in decision making for public relations tasks and responsibilities - Safiah Masbaka,; Syahruddin Awang Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The main concern in the context of ethical issues in public relations practice is, it is conceptualized based on descriptive and normative ethics where personal evaluation and collective evaluation of ethical situations respectively applied in decision making and this study managed to highlight the statistical relationship between personal and organizational factors in ethical decision-making among public relations practitioners, focusing on a locality of Kota Kinabalu, Sabah. The data is based on the questionnaire on public relations practitioners’ ethical decisions that include the criteria of intention consideration, reasoning, and judgment, hence their ethical evaluation is used as the parameter to measure personal ethics. On the other hand, ethical climate reflects a collective perception of ethics in an organization, therefore used as the parameter to measure organizational ethics. A total of n=100 practitioners in Kota Kinabalu, Sabah was participating in this study. The data is tested using Pearson Correlation analysis. The result shows that practitioners’ ethical evaluation has a statistically significant correlation with organizational ethical climate at r=0.314 and p<0.01, which is positive but moderately weak. This correlation indicates that personal and organizational ethics has a weak but positive correlation, and the correlation is statistically significant. The finding conclude that the weak correlation insinuates conflicting the ethical perceptions on both individual and organizational aspects. It can be summarized that the proactive measures can be applied to increase the consistency in criteria of personal ethics as well as the ethical climate of the organization in the pursuit of excellence in public relations.